Computed modeling of humeral mid-shaft fracture treated by bundle nailing. Issue 13 (2nd October 2016) - Obruba, Petr; Capek, Lukas; Henys, Petr; Kopp, Lubomir
Abstract: Elastic bundle nailing is a method for simple humeral mid-shaft fracture osteosynthesis. The aim of our subsequent numerical simulations was to find out torsional and bending stiffness of an elastic bundle nailed humerus. Parametrical 3D numerical model was developed. The diameter of nails was the varying parameter of 1.8, 2.5, 3 and 4 mm. From our results can be seen that the bending stiffness in bundle nailing technique does not depend on nail diameter. On the contrary the torsional stiffness does highly depend on nail diameter. The dependency of the maximal stress on a nail diameter during bending and torsion of the humerus is non-linear. It can be seen that the higher diameter is used the higher stress occurs. Achieved results allow us for the recommendation of optimal nail diameter for this method, which lies between 2 and 3 mm.